120 years of excellence in service to Mining. - Musingwini, C. (The Southern African Institute of Mining and Metallurgy., 2017)
The Wits School of Mining Engineering, which is celebrating 120 years of service to the mining industry, is the seed from which the University of the Witwatersrand grew, and is now the largest mining school in the English-speaking world.
This summary was prepared by Sally Braham on behalf of: Prof Cuthbert Musingwini, Head of the School of Mining Engineering at the University of the Witwatersrand.
Keywords: University of the Witwatersrand; Wits School of Mining; Musingwini, Cuthbert; Mining research; Mining teaching; Mining Industry